2012
DOI: 10.1182/blood-2012-06-437178
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors in hematopoietic cell transplantation survivors: role in development of subsequent cardiovascular disease

Abstract: Hematopoietic cell transplantation (HCT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
190
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 188 publications
(197 citation statements)
references
References 45 publications
3
190
2
2
Order By: Relevance
“…These data extend information provided by previous studies completed in childhood HSCT survivors earlier in follow-up after transplant, or in combined cohorts of pediatric and adult HSCT recipients. For example, Bajwa et al reported dyslipidemia in 13% of 160 childhood HSCT survivors 7 years after transplant 19 ; Armenian et al, in a cohort of 1885 pediatric and adult HSCT survivors, reported 35.6% with hypertension, 16.8% with diabetes, and 43.7% with dyslipidemia 5 years posttransplant 20 ; and Chow et al, in a cohort of 2362 pediatric and adult HSCT survivors, reported 33.9% with dyslipidemia, 27.9% with hypertension, and 14.3% with diabetes 11 years posttransplant. 21 The prevalence of clinically ascertained frailty among adult survivors of childhood hematological malignancies treated with HSCT in this cohort was 7% compared with 1.6% among survivors treated with conventional therapy.…”
Section: Resultsmentioning
confidence: 99%
“…These data extend information provided by previous studies completed in childhood HSCT survivors earlier in follow-up after transplant, or in combined cohorts of pediatric and adult HSCT recipients. For example, Bajwa et al reported dyslipidemia in 13% of 160 childhood HSCT survivors 7 years after transplant 19 ; Armenian et al, in a cohort of 1885 pediatric and adult HSCT survivors, reported 35.6% with hypertension, 16.8% with diabetes, and 43.7% with dyslipidemia 5 years posttransplant 20 ; and Chow et al, in a cohort of 2362 pediatric and adult HSCT survivors, reported 33.9% with dyslipidemia, 27.9% with hypertension, and 14.3% with diabetes 11 years posttransplant. 21 The prevalence of clinically ascertained frailty among adult survivors of childhood hematological malignancies treated with HSCT in this cohort was 7% compared with 1.6% among survivors treated with conventional therapy.…”
Section: Resultsmentioning
confidence: 99%
“…10 Allogeneic HCT recipients are at an increased risk for CVRFs; the 10-year cumulative incidence of hypertension, diabetes, and dyslipidemia is 37.7%, 18.1%, and 46.7%, respectively; the risk for multiple (Ն2) CVRFs approaches 40%. 2 Conditioning with total body irradiation (TBI) is associated with an increased risk of dyslipidemia and diabetes. 2,11 Corticosteroids and calcineurin inhibitors used to manage GVHD also increase the risk of CVRFs.…”
Section: Arterial Diseasementioning
confidence: 99%
“…1 However, HCT survivors are at risk of developing long-term complications such as cardiopulmonary compromise, musculoskeletal disorders, endocrinopathies, and subsequent malignancies. [2][3][4][5] The risk of these complications is influenced by pre-HCT therapeutic exposures, transplantation-related conditioning, and posttransplantation management of GVHD. These complications have a direct impact on the morbidity and mortality experienced by HCT survivors.…”
Section: Introductionmentioning
confidence: 99%
“…В связи с чем од-ним из ведущих рисков у пациентов с гематологиче-скими, онкологическими и иными заболеваниями, требующими ХТ, а также ТГСК, является патология сердца, которая может встречаться у них в 13 раз чаще, чем у здоровых сиблингов [41]. Особенности строения тканей сердца и сосудов делают их крайне восприим-чивыми не только к факторам лечения, предшеству-ющим ТГСК (ХТ и ЛТ), но и повреждению во время трансплантации (кондиционирование, цитокиновые реакции, иммуноопосредованные повреждения).…”
Section: сердечно-сосудистая системаunclassified
“…и воздействия химиопрепаратов, наиболее значимые из которых -антрациклины (например, доксо-или даунорубицин), и тотального облучения тела (ТОТ) [41]. Определен-ное воздействие оказывают и высокие дозы цикло-фосфамида, в особенности при наличии иных пред-располагающих факторов (например, при системном склерозе) [43].…”
Section: сердечно-сосудистая системаunclassified